The effect of real-time teleconsultations between hospital-based nurses and patients with severe COPD discharged after an exacerbation. (December 2013) - Sorknaes, Anne Dichmann; Bech, Mickael; Madsen, Hanne; Titlestad, Ingrid L; Hounsgaard, Lise; Hansen-Nord, Michael; Jest, Peder; Olesen, Finn; Lauridsen, Joergen; Østergaard, Birte
Summary: We investigated the effect of daily real-time teleconsultations for one week between hospital-based nurses specialised in respiratory diseases and patients with severe COPD discharged after acute exacerbation. Patients admitted with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) at two hospitals were recruited at hospital discharge. They were randomly assigned to intervention or control. The telemedicine equipment consisted of a briefcase with built-in computer including a web camera, microphone and measurement equipment. The primary outcome was the mean number of total hospital readmissions within 26 weeks of discharge. A total of 266 patients (mean age 72 years) were allocated to either intervention (n = 132) or control (n = 134). There was no significant difference in the unconditional total mean number of hospital readmissions after 26 weeks: mean 1.4 (SD 2.1) in the intervention group and 1.6 (SD 2.4) in the control group. In a secondary analysis, there was no significant difference between the two groups in mortality, time to readmission, mean number of total hospital readmissions, mean number of readmissions with AECOPD, mean number of total hospital readmission days or mean number of readmission days with AECOPD calculated at 4, 8, 12 and 26 weeks. Thus the addition of one week of teleconsultations between hospital-based nurses and patients with severe COPD discharged after hospitalisation did not significantly reduce readmissions or affect mortality.